Catch enlargement and distribution expansion of the alien fish Hollowsnout grenadier Coelorinchus caelorhincus in the Syrian marine waters (Eastern Mediterranean) - Hussein, Chirine (Latakia University Journal -Biological Sciences Series, 2023)
The aim of this research is to study the catch increase and habitat expansion of Coelorinchus caelorhincus (Risso, 1810) in the Syrian coast. Fish samples were collected on 25 Jan. 2023 in the marine waters facing Banyas city, Syria, using special gillnet (16mm mesh size), with assistance of a fishing boat (9.5m). This species has interred from the western Mediterranean; It had been recorded in 2016 from the Syrian marine water (Lattakia coast) as a single individual. In this year, 2023, it appeared in Banyas coast of the Syrian waters, in a group of 30 individuals with an average length of (16.39±1.75) cm. Catching such number of individuals at one fishing trip gives an indication that this species may have already established itself in the Syrian marine waters, and expanded its distribution to the south within the Syrian coast. Thus, this species may have become a threat to the native fish population through competition for food and for space.